The Immediate And Post Flood Mid-Term of Flood Victims-Psychospiritual Module - Muhammad Idris Bullare @ Bahari; Adeymend Reny Japil; Rosnah Ismail; Mohd. Dahlan A. Malek; Jasmine Adela Mutang; Lailawati Madlan @ Endalan; Wan Anor Wan Sulaiman; Fattin Navilla Abdul Ghani (2018)
The exploration of the psychological aspect of flood victims and the needs for development of a psychological module for such victims is vital especially after a major flood incident. However, there are no consensus on the availability of interventions that could be applied at an instant to address the traumatic experiences immediately or a short while after a flood incident. The purpose of this study is to develop a Flood Victims-PsychoSpiritual Module (Modul PsikoSpiritual-Mangsa Banjir; MPS-MB) that will be applied to flood victims in Sabah and Sarawak as well as Peninsular Malaysia. A total of 14 flood victims in Gua Musang, Kelantan and Kuching, Sarawak have been recruited in this investigation. Participants were selected from recorded victims registered under the flood victim relocation center. The study has adopted the exploratory sequential design which includes Phase 1: Qualitative study, the Interim Phase: Module development process, and Phase 2: Validation of the module by an expert of disaster psychology. There are five strategies which serve as the core of the development of the MPS-MB which are 1) understanding trauma, 2) the psycho-social strategies in combatting trauma, 3) the hope strategy, 4) the spiritual/religious strategy, and 5) the counseling and therapy strategy. The content validity of the MPS-MB were conducted by an expert in psychology. The MPS-MB is able to generate an in-depth understanding of the authentic psycho-spiritual experiences of flood victims. The module would empower the society, especially flood victims to take precaution in managing and minimizing the psychological impacts of flood incident.